2016
DOI: 10.1111/jai.13142
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships of six species of the genera Cobitis and Sabanejewia (Cobitidae) in Iranian river systems

Abstract: Summary Length‐weight relationships (LWRs) were estimated for six spined loach species from Iran. Data were collected between 2010 and 2015. These represent the first reports of length–weight data for five of the species (Cobitis avicennae, Cobitis faridpaki, Cobitis keyvani, Sabanejewia aurata and Sabanejewia caspia) while also providing additional data on the remaining species (Cobitis linea). Five of these species are endemic and the remaining S. caspia, is native to the country. Estimated b values obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Several studies have reported positive allometric growth of Cobitis fish (Boroń et al 2008;Patimar et al 2011). In particular, Cobitis keyvani Mousavi-Sabet, Yerli, Vatandoust, Özeren et Moradkhani, 2012 from the Sefid-rud River of Iran showed a b value of 3.411 (Mousavi-Sabet et al 2016), which is similar to our result. Nevertheless, more detailed investigations are needed to verify this result, and it seems reasonable to refer to our results as a case study from a specific fish population.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported positive allometric growth of Cobitis fish (Boroń et al 2008;Patimar et al 2011). In particular, Cobitis keyvani Mousavi-Sabet, Yerli, Vatandoust, Özeren et Moradkhani, 2012 from the Sefid-rud River of Iran showed a b value of 3.411 (Mousavi-Sabet et al 2016), which is similar to our result. Nevertheless, more detailed investigations are needed to verify this result, and it seems reasonable to refer to our results as a case study from a specific fish population.…”
Section: Discussionsupporting
confidence: 89%
“…It is well known that the functional regression b value represents the body form of fish (Kalayci, Samsun, Bilgin, & Samsun, ; Mousavi‐Sabet, Heidari, & Paknejad, ; Ricker, ), and is affected by a number of factors such as gonad maturity, sex, diet, stomach fullness, health, age, fishing time as well as the area and fishing vessels (Mousavi‐Sabet, Heidari, Abbasi, & Vatandoust, ; Mousavi‐Sabet, Heidari, & Fekrandish, ; Wootton, ); however, these factors were not considered in the present study. The narrow sample size or the length range possibly affected the b values of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in b ‐values can be attributed to the combination of one or more factors: (i) differences in the number of specimen examined, (ii) area/season effect, and (iii) differences in the observed length ranges of the specimens caught (Moutopoulos and Stergiou, ; Mousavi‐Sabet, Heidari, Mohamadi‐Darestani, Mansouri‐Chorehi, & Ghasemzadeh, ; Mousavi‐Sabet, Heidari, Abbasi, & Vatandoust, ).…”
Section: Discussionmentioning
confidence: 99%